The impact of a training curriculum to develop physical abilities and the relationship subtly correction term jumping handball - Salman Aaessa, Najah (Journal of Physical Education, 2012)
Contributed to applied science and sports training programs in the planning and began intense competition between countries to devise the means of modern scientific levels contribute to the development of sports for all sporting events as well as conducting research and numerous studies and attention to factors that are related to the basic performance skills.And a game of handball sports that require physical capabilities of a private, one of the most important pillars on which the player and this game requires speed to move the pitch and the ability of muscle of the Parties to the upper and lower during jumping and scoring. Therefore, the importance of speed in transition and explosive power and power deals as quickly as elements to be the player handball that possess in order to achieve an excellent level and the results as good as the training curricula inhalers and carried out regularly occur rapid developments and regularly in physical abilities and skill in sports, and up to achieve the goals of the training process.The study aimed to identify the impact of the curriculum proposed in the development of certain physical abilities and skill correction term either by jumping hypotheses there is a positive impact of the training curriculum in the development of some special physical abilities on the skill of jumping out of the correction term players handball University of Technology. Was used experimental method to achieve the objectives of the research consisted sample players elected University of Technology, handball and the number (12) players, and included measures research field tests tribal and conducted on 14_3 _2011 and then was applied curriculum set out in the Annex (2) for the period from 15_3_2011 until 14_6_2011 and then applied a posteriori tests on 16_6_ 2011 under the same conditions that applied by the tribal tests.After processing the results statistically concluded:-The curriculum for the training have a positive impact in the development of physical abilities, which is (explosive power of the arms and legs, distinctive force as soon as the arms and legs, speed, accuracy correction) correction term associated with the skill of the players jumping team handball University of Technology.-Therefore, the researcher recommends the need to focus on the elements of physical preparation yet to be proven on the importance of the skill level players handball University of Technology.